2012
DOI: 10.1089/end.2011.0671
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Bubble Cavitation by Modifying the Diffraction Wave from a Lithotripter Aperture

Abstract: Purpose: A new method was devised to suppress the bubble cavitation in the lithotripter focal zone to reduce the propensity of shockwave-induced renal injury. Materials and Methods: An edge extender was designed and fabricated to fit on the outside of the ellipsoidal reflector of an electrohydraulic lithotripter to disturb the generation of diffraction wave at the aperture, but with little effect on the acoustic field inside the reflector. Results: Although the peak negative pressures at the lithotripter focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is known that the shock wave emitted by a collapsing bubble is quite distinct from other underwater shock waves, such as generated for lithotripsy, 14 or when a laser pulse is focused into a liquid, to generate a laser-induced bubble 15 [see Fig. 12(a) in the Appendix].…”
Section: The Bubble Collapse Shock Wavementioning
confidence: 99%
“…It is known that the shock wave emitted by a collapsing bubble is quite distinct from other underwater shock waves, such as generated for lithotripsy, 14 or when a laser pulse is focused into a liquid, to generate a laser-induced bubble 15 [see Fig. 12(a) in the Appendix].…”
Section: The Bubble Collapse Shock Wavementioning
confidence: 99%
“…Another strategy for minimizing vascular injury is to reduce the intraluminal bubble expansion by modifying the profile, sequence, and spatial distribution of LSW, such as with in situ pulse superposition to the LSW tensile wave [37,38], inver sion of LSW using a pressure release reflector [39][40][41], use of an acoustic diode to reduce the amplitude of the tensile wave [42], and modifying the diffraction wave from the lithotripter aperture by an edge blocker and consequently decreasing its contribution to the LSW tensile wave at the focal region [43]. Since the maximum bubble size in a free field is proportional to bubble collapse time, the reduction of bubble cavitation was usually verified by PCD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been demonstrated that the sonoporation pore size is highly correlated with acoustic driving parameters, e.g ., acoustic pressure, sonication duration time and pulse repetition frequency 11 , 24 26 . Heterogeneous cellular membrane permeability variations have also been observed at different microbubble-cell distance 27 , 28 , bubble size 23 and microbubble-cell numbers 29 , 30 . However, these studies mainly explored the membrane-level responses to microbubble-mediated sonoporation and did not fully illuminate the impacts of acoustic driving parameters and microbubble-to-cell relative parameters on deeper cellular structures, such as the cytoskeleton.…”
Section: Introductionmentioning
confidence: 86%